Role of environmental toxicants in the development of hypertensive and cardiovascular diseases. (2022) - Habeeb, Ehsan; Aldosari, Saad; Saghir, Shakil A.; Cheema, Mariam; Momenah, Tahani; Husain, Kazim; Omidi, Yadollah; Rizvi, Syed A.A.; Akram, Muhammad; Ansari, Rais A.
Abstract: The incidence of hypertension with diabetes mellitus (DM) as a co-morbid condition is on the rise worldwide. In 2000, an estimated 972 million adults had hypertension, which is predicted to grow to 1.56 billion by 2025. Hypertension often leads to diabetes mellitus that strongly puts the patients at an increased risk of cardiovascular, kidney, and/or atherosclerotic diseases. Hypertension has been identified as a major risk factor for the development of diabetes; patients with hypertension are at two-to-three-fold higher risk of developing diabetes than patients with normal blood pressure (BP). Causes for the increase in hypertension and diabetes are not well understood, environmental factors (e.g., exposure to environmental toxicants like heavy metals, organic solvents, pesticides, alcohol, and urban lifestyle) have been postulated as one of the reasons contributing to hypertension and cardiovascular diseases (CVD). The mechanism of action(s) of these toxicants in developing hypertension and CVDs is not well defined. Research studies have linked hypertension with the chronic consumption of alcohol and exposure to metals like lead, mercury, and arsenic have also been linked to hypertension and CVD. Workers chronically exposed to styrene have a higher incidence of CVD. Recent studies have demonstrated that exposure to particulate matter (PM) in diesel exhaust and urban air contributes to increased CVD and mortality. In this review, we have imparted the role of environmental toxicants such as heavy metals, organic pollutants, PM, alcohol, and some drugs in hypertension and CVD along with possible mechanisms and limitations in extrapolating animal data to humans. Highlights: Rising incidence of hypertension may be linked to chronic exposure with environmental toxicants. Urban lifestyle and alcohol intake may be responsible for increased incidence of hypertension among urbanites. Exposure with organic solvent, heavy metals and pesticides could also be contributing to the rise in blood pressure.